Corporate Humanities in Higher Education Moving Beyond the Neoliberal Academy - Leo, Jeffrey R. Di.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
How do humanists speak for and from the humanities in an academy which values them less and less and market-driven approaches more and more? Jeffrey R. Di Leo provides a thorough critique of the higher education crisis and a set of practical and reasonable remedies for shaping the study and practice of the humanities in the academy of the future.
Keywords: Philosophy; Philosophy and social sciences; Educational sociology; Higher education; Education -- Philosophy; Social sciences; Education and sociology; Sociology, Educational; Philosophy; Philosophy of Education; Social Sciences, general; Higher Education; Educational Philosophy; Sociology of Education